Students' Critical Thinking and Mathematical Problem Solving Skills through the Problem Based Learning (PBL) Model and Guided Inquiry at SMA Negeri 5 Lebong - Jeli Dahliah; Apriza Fitriani; Risnanosanti (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine whether there are differences and influences on students' critical thinking and mathematical problem-solving abilities through the Problem Based Learning (PBL) and Guided Inquiry models at SMA Negeri 5 Lebong. The population of this study was all grade X students of SMA Negeri 5 Lebong. The sampling technique used cluster random sampling, namely random sampling based on class, so that three sample classes were obtained, each consisting of 33 students, namely class X.1, X.2, and X.5 with a total of 99 students. The type of research used was quasi-experimental. Data collection was carried out using essay tests to measure students' critical thinking and mathematical problem-solving abilities. Data were analyzed using the One Way ANOVA test. The results of the study showed that there were significant differences in students' critical thinking and mathematical problem-solving abilities between classes using the PBL, Guided Inquiry and Conventional Learning models. The Guided Inquiry model was more effective in improving critical thinking abilities and the PBL model showed more effectiveness in improving students' mathematical problem-solving abilities. Abstrak Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan dan pengaruh kemampuan berpikir kritis dan pemecahan masalah matematis siswa melalui model Problem Based Learning (PBL) dan Inkuiri Terbimbing di SMA Negeri 5 Lebong. Populasi penelitian ini adalah seluruh siswa kelas X SMA Negeri 5 Lebong. Teknik pengambilan sampel menggunakan cluster random sampling, yaitu pengambilan sampel secara acak berdasarkan kelas, sehingga diperoleh tiga kelas sampel, masing-masing berjumlah 33 siswa, yaitu kelas X.1, X.2, dan X.5 dengan total 99 siswa. Jenis penelitian yang digunakan adalah quasi eksperimen. Pengumpulan data dilakukan dengan menggunakan test essay untuk mengukur kemampuan berpikir kritis dan kemampuan pemecahan masalah matematis siswa. Data di analisis menggunakan uji One Way Anova. Hasil penelitian menunjukan bahwa terdapat perbedaan yang signifikan kemampuan berpikir kritis dan pemecahan masalah matematis siswa antara kelas menggunakan model PBL, Inkuiri Terbimbing dan Pembelajaran Konvensional. Model Inkuiri Terbimbing lebih efektif untuk meningkatkan kemampuan berpikir kritis dan Model PBL Menunjukan lebih efektif dalam meningkatkan kemampuan pemecahan masalah matematis siswa.